Single lithography-step self-aligned fabrication process for Vertical-Cavity Surface-Emitting Lasers. (April 2017) - Marigo-Lombart, Ludovic; Arnoult, Alexandre; Mazenq, Laurent; Dubreuil, Pascal; Reig, Benjamin; Mauran, Nicolas; Thienpont, Hugo; Panajotov, Krassimir; Almuneau, Guilhem
Abstract: We demonstrate a self-aligned process to fabricate Vertical-Cavity Surface-Emitting Lasers (VCSEL) which combines, within a single lithographic step the mesa etch, the surface passivation, the opening of the emission window and the top annular metallization. This process flow, based on a double photoresist layer enabling two lift-off steps, offers great advantages such as easy and fast implementation while insuring a perfect alignment between the emitting window, the passivation layer aperture and the metal-ring contact. VCSEL fabrication is drastically simplified and its repeatability improved. Finally, this process can be advantageously applied to other photonic devices such waveguide-ridge lasers, modulators, LED, etc.